STRUGGLE OF BLACK WOMEN REFLECTED IN BERNARDINE EVARISTO’S GIRL, WOMAN, OTHER - Gabriela Pantow; Agustine C. Mamentu; Elizabeth Z. Oroh (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this research is to describe struggle of black women in Bernardine Evaristo’s Girl, Woman, Other. There are three kinds of struggle that the researcher found such as black women’s struggle against racism, society’s prejudice, and gender oppression. Due to the fact that the data are presented in the form of words, this study is qualitative. Napikoski's feminist literary theory will be utilized for the data analysis. The novel itself served as the primary source for the data collection, and various books, journals, web pages, and other references were used as secondary sources to support the research. The novel's context and interpretation of the text serve as the foundation for the concept's analysis. The result of this study shows how black women struggling with racism, society’s prejudice and also gender oppression.